2015
DOI: 10.4103/1463-1741.153403
|View full text |Cite
|
Sign up to set email alerts
|

Occupational noise and myocardial infarction: Considerations on the interrelation of noise with job demands

Abstract: The present analysis aims to differentiate the association of noise on myocardial infarction (MI) by job specific demands using International Standard Classification of Occupations (ISCO)-88 codes as a proxy. Data of a German case-control study were supplemented by job descriptions (indicated by ISCO-88). It was examined whether the demands in the various occupational groups modify the effect of noise. Noise and occupational groups are combined to form new exposure categories. Conditional logistic regression m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 38 publications
0
33
0
1
Order By: Relevance
“…In the study of Stokholm et al the risk was RR = 1.17, 95% CI: 1.09-1.26 among women and RR = 1.06, 95% CI: 0.98-1.14 among men [31]. In that of Kersten and Backé men were, in fact, not found to be at risk [32]. Gan et al, on the contrary, reported statistically significantly elevated odds of coronary heart disease only among male workers [8].…”
Section: Discussionmentioning
confidence: 94%
“…In the study of Stokholm et al the risk was RR = 1.17, 95% CI: 1.09-1.26 among women and RR = 1.06, 95% CI: 0.98-1.14 among men [31]. In that of Kersten and Backé men were, in fact, not found to be at risk [32]. Gan et al, on the contrary, reported statistically significantly elevated odds of coronary heart disease only among male workers [8].…”
Section: Discussionmentioning
confidence: 94%
“…[42] specifically surveyed blue-collar workers, and Dimitrova and Karaslavova[39] included hospitalized patients and controls who underwent prophylactic examinations. Five articles reported summary risks for both the genders and four analyzed male-only samples; for Kersten and Backé[19] and Dimitrova and Karaslavova,[39] we extracted the effect sizes for males.…”
Section: Resultsmentioning
confidence: 99%
“…[42] collected detailed occupational histories and classified participants’ exposure based on “measurements made by hygienists in the 1970–1975 period (when available), or by extrapolation from measurements made for jobs with similar conditions”. Kersten and Backé[19] estimated daily exposure levels for 10 years, retrospectively, “from information about workplaces and machines with the help of catalog specifications”. The method for objective noise assessment was not reported in the article by Jovanovic et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations